Regeneration in permanent immature necrotic tooth –a case report - Shubham, Snigdha; Nepal, Manisha (Journal of Chitwan Medical College, 2020)
Immature necrotic teeth pose a challenge to endodontist. To simplify this challenge regenerative endodontic has gained popularity these days. This approach is based on triggering stem cells and repopulate over scaffold to induce regeneration of pulp like tissue. This case report presents a case of regeneration of apical tissue with significant healing of periapical lesion.